Flowering Behavior, Fruit Harvesting Age and Proximate Levels of the Flesh of the West Sumatera Superior Avocado - farihul ihsan; Sri Hardiati; Ni Luh Putu Indriyani (UNIVERSITAS NEGERI PADANG, 2023)
The aim of this study was to determine flowering behavior, fruit harvesting age and proximate levels of the flesh of the four West Sumatera superior avocado varieties, i.e: Mega Gagauan, Mega Murapi, Mega Paninggahan and Tongar. The research was conducted in Indonesian Tropical Fruit Research Institute from October 2020 to August 2022. The plant materials was used Mega Gagagauan, Mega Murapi, Mega Paninggahan and Tongar which 2 trees each variety. Parameters observed i.e: flower type, blooming time, fruit age, fruit character, and proximate content of flesh. Data were analyzed descriptively. The results showed that Mega Gagauan, Mega Murapi and Mega Paninggahan had type B flowers, while Tongar had type A flowers. The time difference between the first and second blooms on the same day for Mega Gagauan and Mega Murapi was 1 and 2 hours, while there is no time difference in Mega Paninggahan and Tongar. The fruits harvesting age of Mega Gagauan, Mega Murapi, Mega Paninggahan, and Tongar are i.e: 161; 232; 160; and 170.42 days. Tongar had the lowest water content (73.83%) and the highest fat (15.30%), Mega Murapi had the lowest crude fiber content (2.82%), and Mega Paninggahan had the highest protein content (1.87%). Mega Paninggahan was considered the best variety based on the observed character and this research data can be used as the basic for determining actions of cultivating avocado plant.